Evaluation of Beriman’s Terminal Retribution at Tomohon City - Munaiseche, Stefano Yohanes; Dilapanga, Abdul Rahman; Sendouw, Recky Herold Elby; Mandagi, Marthinus (Technium Social Sciences Journal, 2022)
Evaluation is a process of renewal activity, namely making efforts to make something more appropriate or suitable to the needs for the better or valuable. The terminal levy is a terminal levy as one of the business service fees collected by the regional government to any individual or private entity that utilizes terminal services that carry people or goods by public transportation. Understanding the terminal, before arriving at the terminal analysis then very needs to understand the function of a terminal. By understanding the terminal function, it is hoped that the understanding of the terminal will be more in-depth to facilitate the analysis. The function of the terminal is to provide means of entry and exit for driven objects, passengers, or vehicles goods to or leave the system. Terminal functions were like the description from terminal function automatically overall on all system models transportation. This study analyzes the retribution process at Beriman Terminal type B in Tomohon. The evaluation method was carried out using a qualitative method with the type of research, namely phenomenology. The informants in this study were 14 respondents as key informants. The research data were obtained from various data sources, namely primary and secondary data. Data was collected through interviews, documentation, and observation. Data reduction, presentation, and conclusion drawing are the data analysis techniques used. The data validation technique used is the source, technique, and time triangulation. The results of this study indicate that the management of the type B Terminal retribution in Tomohon city in September 2021 Tomohon is almost optimal. Based on several management indicators in this study, namely: 1) planning, not achieving the target of retribution and inadequate facilities and infrastructure, 2) organization, division, and work procedures are by their respective fields, 3) implementation, procedures carried out are by regulations and is carried out appropriately and adequately 4) supervision, supervision is carried out regularly and properly.